Parent-child communication affecting the productive health knowledge of adolescents from Colegio San Agustin-Bacolod. - Tagubar, Zoe Kahilelle L.
This study examined the reproductive health knowledge of adolescents through communication with their parents. The focused group discussions revealed that adolescents receive warnings and values about sex rather than the proper expalnation of the topics falling under reproductive health. Other sources such as books, schools and friends are preffered by adolescents on getting information about reproductive health. There is also a difference in the information that the father and mother relays on their adolescent children. It was also found put that although, parents are perceived as not knowledgeable on reproductive health. Religion also affects the understanding of adolescents about the reproductive health. Results also showed that adolescents want to know more about topics that are considered taboo in their families and these are : contraceptives, condom use and homosexuality. Lastly, adolescents are willing to share what they have learned to other people but greatly depends on the gae of the person about the topics on reproductive health.